TECHNICAL ANALYSIS OF IRRIGATION SYSTEMS FOR COFFEE (Coffea arabica L.) IN THE WESTERN REGION OF BAHIA - Vicente, Marcelo Rossi; Mantovani, Everardo Chartuni; Fernandes, André Luís Teixeira; Vieira, Gustavo Haddad Souza; Sediyama, Gilberto Chohaku; Figueredo, Edmilson Marques (Coffee Science - ISSN 1984-3909, 2011)
This study aimed to evaluate the uniformity of 27 irrigation systems with 7 as drip and 20 as central pivot, located in 12properties distributed in three counties of western Bahia. Of the 20 central pivot irrigation systems evaluated, 11 were equipped withsprinklers such as “Low Energy Precision Application” (LEPA), five with alternative sprinklers and four conventional sprinklers. Wedetermined the Christiansen Uniformity Coefficient (CUC) and the coefficient uniformity of distribution (CUD) of each system. Of thecentral pivots evaluated, only two (10%) had CUC values below 80%, which is considered unsuitable. Of the seven drip irrigationsystems evaluated, only one showed an unacceptable CUD value. The average value of CUD found during the evaluations, for thecentral pivot irrigation system with sprinklers equipped with LEPA was higher than the value given by drip. The central pivots withlocalized application (LEPA and alternative) had higher values of uniformity than the conventional central pivots.